The Importance of European Languages for Russian Scientific Contacts with the Global South - Alexey V. Kuznetsov (Современная Европа)
In recent years, Russia has been rapidly turning towards the East and the global South as a whole. First of all, the country's changed foreign policy priorities and shifts in the geography of its foreign trade attract attention, but there is also an intensification of Russian scientific ties with a number of developing countries. At the same time, there are many difficulties with the development of scientific contacts with the countries of the Global South, and the essential issue is to develop the right strategy to minimize existing language barriers. The article shows the growing, but still limited role of the English language in scientific activity. It is demonstrated that states with a fairly large population and a developed R&D sector sometimes do not take minimal steps themselves to preserve any significant role of the national language in scientific activity, which is especially important to understand in contemporary Russia. At the same time, the languages of the former European metropolises, not only English, but also French, Spanish and Portuguese, play an important role in the scientific life of many countries of the Global South. In this regard, the successful positioning of Russian research organizations and their achievements requires a combination of the use of “main” European languages in scientific contacts with partners in the Global South with a gradual expansion of the number of Russian specialists with knowledge of Oriental languages. A separate task, and one that allows to find new solutions in the digital age, is to promote the Russian-language segment of publications abroad. Among other things, this area of application of “soft power” can be carried out through the preparation of thematic English-language bibliographies.